2015
DOI: 10.1515/msp-2015-0054
|View full text |Cite
|
Sign up to set email alerts
|

Growth of intermetallic compound between indium-based thermal interface material and copper substrate: molecular dynamics simulations

Abstract: The diffusion phenomenon occurring between copper and indium was investigated by molecular dynamics simulations. The calculations were carried out in various temperatures in aging domain with the use of the commercially available Materials Studio v.6. software. The results showed that the intermetallic compound (IMC) growth followed the parabolic law, which indicated this growth to be mainly controlled by volume diffusion. The growth activation energy was estimated at 7.48 kJ·mol −1 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…20) A large variety of different CMP polishing pads exists, for which a qualitative division into four different types, based on their composition, porosity type and hardness, was given by James (2004) 9) and updated by Lawing (2020). 23) In this qualification, the hard polyurethane CMP pad type "Visionpad 5000" (supplier: Dupont) used in our study, belongs to the class "Type 3" of hard filled polymer sheet pads with uniform porosity, which among other uses, are applied for metal Table I. Overview of some available values for different hardness types (Mohs, 8) Brinell, Vickers, and Berkovich nanoindentation hardness) for indium and some other relevant metals for which CMP processes have already been developed.…”
Section: Methods: Tools and Materials Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…20) A large variety of different CMP polishing pads exists, for which a qualitative division into four different types, based on their composition, porosity type and hardness, was given by James (2004) 9) and updated by Lawing (2020). 23) In this qualification, the hard polyurethane CMP pad type "Visionpad 5000" (supplier: Dupont) used in our study, belongs to the class "Type 3" of hard filled polymer sheet pads with uniform porosity, which among other uses, are applied for metal Table I. Overview of some available values for different hardness types (Mohs, 8) Brinell, Vickers, and Berkovich nanoindentation hardness) for indium and some other relevant metals for which CMP processes have already been developed.…”
Section: Methods: Tools and Materials Characterizationmentioning
confidence: 99%
“…4) Blanket wafers plated for the tests contained 175 nm TiW liner and 25 nm Cu seed underneath, deposited through PVD, directly on Si. It should be noted that the 25 nm Cu seed layer, which aids the initial indium plating, 4) was presumably taken up into the In layer through diffusion, forming partial CuIn 2 intermetallic compound 23) regions at the bottom of the indium layer. 4) The patterned wafers contain dies with squares consisting of large numbers of circular test and dummy trench bond pad structures, which lie close to each other, with pitches 5.0, 7.0, 10.0 and 20.0 μm (see Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the different settings of reaction conditions and the ratio of different metals, AgIn 2 can react with excess Ag to form Ag 2 In when In is completely consumed, enriching the variety of IMCs and enhancing the adaptability to different states. 68 The growth of IMC at the interface between pure copper and indium was investigated by building a suitable model and performing molecular dynamics simulations, 69 and it was found that the growth of IMC is mainly controlled by volume diffusion (Fig. 11a).…”
Section: Chemical Interfacial Interactionsmentioning
confidence: 99%
“…Therefore, In-based solders with low melting temperatures have been essentially used for soldering [26,27]. However, the interface between the In-based solder and the Cu UBM is a layer of Cu-In intermetallic compounds, not Cu-Sn IMC [28][29][30]. The interfacial reaction between the solder and UBM is controlled by their inter-diffusion.…”
Section: Introductionmentioning
confidence: 99%